Temporal and Spatial Population Genetic Variation in Chilean Jack Mackerel (Trachurus murphyi) - Cristian B. Canales-Aguirre; Sandra Ferrada Fuentes; Ricardo Galleguillos (Biology)
Trachurus murphyi have been studied for population genetic structures for decades, identifying only one large population across the South Pacific Ocean. Although all of these studies have extensively examined the spatial genetic pattern, there remains a gap in understanding the potential role of temporality. Our study aims to elucidate spatial and temporal genetic patterns in T. murphyi populations in the South Pacific Ocean, examining genetic composition across seasons, including feeding and spawning seasons, where the latter was not previously investigated. Using 10 microsatellite loci, our study confirms an overall consistent and stable population genetic pattern in T. murphyi across its geographic distribution observed over multiple years and seasons. The only exception was found for New Zealand in the spring–summer season. Furthermore, we identify potential genetic markers for monitoring variability in the species.